2012
DOI: 10.3109/08820139.2012.661007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Immuno-Characteristics of Immunoglobulin-like Glycoproteins in Cancer Cell-expressed Biomarker, CA215

Abstract: RP215 monoclonal antibody (Mab) was shown to recognize a specific carbohydrate-associated epitope found in cancer cell-expressed glycoproteins, known as CA215. The membrane-bound and soluble forms of CA215 were detected in almost all of the cancer cells in humans, but rarely found in normal tissues. Through MALDI-TOF MS analysis, it has been reported previously that as much as 40% of the detected tryptic peptides of CA215 showed high degrees of sequence homology to those found in immunoglobulin heavy chains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…By using typical EIA kit for normal human IgG, it was observed that cancerous IgG exhibited a significantly lower immunoactivity than that of normal IgG (1-5% of the normal activity) (Lee et al, 2012b). This phenomenon can only be explained based on the fact that atypical cancerous immunoglobulins are aberrantly glycosylated, resulting in significant alternations in protein structures and immunoactivities of the former.…”
Section: Normal Immunoglobulinsmentioning
confidence: 93%
See 2 more Smart Citations
“…By using typical EIA kit for normal human IgG, it was observed that cancerous IgG exhibited a significantly lower immunoactivity than that of normal IgG (1-5% of the normal activity) (Lee et al, 2012b). This phenomenon can only be explained based on the fact that atypical cancerous immunoglobulins are aberrantly glycosylated, resulting in significant alternations in protein structures and immunoactivities of the former.…”
Section: Normal Immunoglobulinsmentioning
confidence: 93%
“…Furthermore, RP215-epitope(s) were detected in many other unrelated proteins with no mutual homology in their respective amino acid sequences (Lee et al, 2012e). Finally, aberrant glycosylations of cancerous immunoglobulins could result in the creations of RP215-associated "sugar" epitope and low immunoactivity when compared to those of normal human immunoglobulins (Lee et al, 2012b).…”
Section: Glycoanalysis and Glycosylation Site Mapping Of Rp215-specifmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cancerous IgG is believed to be additionally glycosylated as compared to normal IgG, the binding or functional activity of cancer-ous IgG to certain unknown antigens may or may not be affected [44].…”
Section: Molecular Characteristics Of the Carbohydrate-associated Epimentioning
confidence: 99%
“…For example, a significant loss of RP-215 epitope activity was observed when CA215 was treated with mild sodium periodate solution (10 -100 mM) at neutral pH, extreme heat (e.g. 100˚C for 5 min), culturing of cancer cells in serum-free medium, or incubation at extreme pH (≤ 2.0 or ≥12.0) [2][3][4]. This is in contrast to normal human immunoglobulin G (IgG), of which the immunoactivity remained stable under the above conditions [2][3][4].…”
Section: Introductionmentioning
confidence: 99%